2 - Analysis of the Emergence and Development of Private Universities in Nigeria* (1999–2006) - Obasi, Isaac N. (Journal of Higher Education in Africa, 2007)
One of the devastating consequences of the prolonged period of military dictator- ship in Nigeria is the non-development of a private higher education system. How- ever, with the emergence of democratic rule in 1999 and the liberalization of higher education, there has been a surge in the provision of private higher educa- tion. From a modest number of three pioneer private universities in 1999, there were 23 licensed private universities as at June 2005. This article provides an assessment of the development of these universities using the older ones as the basis of empirical analysis. Also, based on the available evidence, the article con- cludes that private universities are currently setting the pace, and serving as a source of positive challenge to the public universities, thereby providing the much- needed healthy competitive environment for the future growth and diversification of the entire higher education system in Nigeria.